Synthesis of Mesoporous Silica Incorporated with Low Iron Concentration and Gelatin Co-Template via The Ultrasonication Method and Its Methylene Blue Photodegradation Performance - Maria Ulfa; Sandini Ajeng Istanti (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
In this work, low iron concentration incorporated on mesoporous silica with gelatin co-template (Fe2O3/GSBA-15) has been successfully synthesized via the ultrasonication method. The physical, chemical, and structural properties of the samples were investigated with X-Ray Diffraction (XRD), Scanning Electron Microscope- Energy Dispersive X-Ray (SEM-EDX), Fourier Transform Infra-Red (FTIR), and N2 adsorption-desorption. Results showed good distribution of low concentration of iron oxide on the gelatin mesoporous silica GSBA-15. Elemental and surface analysis presented that iron oxide incorporation with higher concentration exhibited lower surface area due to the blocking pore. The highest photocatalytic activity on the methylene blue dye degradation was achieved at 10% Fe2O3/GSBA-15 with 80% efficiency. The results revealed that the photocatalytic activity of Fe2O3/GSBA-15 enhanced with the presence of iron oxide. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).